Functional and technological applications of whey proteins in the food industry (Agroindustrial Science, 2026)
Whey is a dairy industry by-product with high nutritional value, mainly due to its protein fraction, composed of β-lactoglobulin, α-lactalbumin, immunoglobulins, lactoferrin, among others. These proteins have functional properties such as solubility, emulsification, gelation and foaming capacity, which allows them to be used in a wide variety of food applications. In the food industry, whey proteins are used in functional beverages, dairy products, baking, meat products and nutritional supplements, improving the texture, stability and nutritional profile of the products. In addition, various studies have highlighted its health benefits, including its role in maintaining muscle mass, modulating the immune system and satiety. However, there are still challenges in its use, such as optimizing extraction methods, consumer perception and the sustainability of its use on a large scale. This review article discusses the protein components of whey, their functional properties and their application in the food industry, highlighting recent innovations and future prospects in this field.
Keywords: Whey; proteins; functional properties; food applications; innovation